Shedding of active tissue factor by aortic smooth muscle cells (SMCs) undergoing apoptosis - Brisset, Anne-Cécile; Terrisse, Anne-Dominique; Dupouy, Dominique; Tellier, Lise; Pech, Stéphane; Navarro, Chantal; Sié, Pierre (Thrombosis and Haemostasis, 2003)
As apoptosis of neo-intimal SMCs is a feature of advanced atherosclerotic plaques, the procoagulant properties of SMCs of synthetic phenotype undergoing apoptosis were investigated. SMCs isolated from rat aorta obtained 10 days after balloon injury, previously found to up-regulate Tissue Factor (TF) and Tissue Factor Inhibitor (TFPI) and to release large amounts of TFPI (Ghrib et al. Thromb Haemost 2002;87:1043-50), were sensitive to the apoptosis induced by Fas-ligand. During this process, surface TF activity rose by a factor 10 over 6 hours, in parallel with a proportional increase in prothrombinase, while TF protein expressed at the membrane significantly decreased. The microparticles (MPs) produced during SMC death bore intact and functional TF, but the release of TFPI did not change, so that the balance shifted to a procoagulant state during apoptosis. Shed MPs enhanced thrombus formation in flowing whole blood over collagen coated-glass slides. Apoptotic SMCs in atherosclerotic plaques represent a reservoir of highly thrombogenic material, released into the blood stream in case of spontaneous or mechanical plaque disruption.
Keywords: Apoptosis; arterial thrombosis; smooth muscle cells; tissue factor